Bis wann bleibt der Kaiser „Kult“? Die Verehrung des Kaiserbildes als Akt der Zivilreligion in der Spätantike - Raschle, Christian R. (Kaiserkult in den Provinzen des Römischen Reiches: Organisation, Kommunikation und Repräsentation, 2016)
The cultic veneration of the Roman imperial house by the provincial population was not only a religious and political affair; It also contains relevant aspects in the field of media, social and economic history. Against the background of new epigraphic and numismatic sources, the contributions of the volume illuminate the imperial cult in the provinces and even outside the empire from its genesis to late antiquity
Keywords: Conference papers and proceedings; Congresses; Emperor worship; Religion; Religion and culture; Religion and politics; Roman provinces; Rome; Rome (Empire)